Properties of concrete containing ground palm oil fuel ash as fine aggregate replacement - Saffuan, Wan Ahmad; Khairunisa, Muthusamy; Norhafizah, A.Mohd; Norhaiza, Nordin (IOP Publishing Ltd, 2017)
Environmental degradation resulting from increasing sand mining activities and disposal of palm oil fuel ash (POFA), a solid waste generated from palm oil mill needs to be resolved. Thus, the present research investigates the effect of ground palm oil fuel ash as partial fine aggregate replacement on workability, compressive and flexural strength of concrete. Five mixtures of concrete containing POFA as partial sand replacement designed with 0%, 10%, 20%, 30% and 40% of POFA by the weight of sand were used in this experimental work. The cube and beam specimens were casted and water cured up to 28 days before subjected to compressive strength and flexural strength testing respectively. Finding shows that concrete workability reduces as the amount of POFA added become larger. It is worth to note that 10% of POFA is the best amount to be used as partial fine aggregate replacement to produce concrete with enhanced strength.